Seed system security assessment : Southern Sudan : November-December 2010 - Food and Agriculture Organization of the United Nations; Sperling, L.; Katungi, E; International Center for Tropical Agriculture; Ministry of Agriculture and Forestry; Government of Southern Sudan; State Ministry of Agriculture and Forestry; Africa Action Help International; Agency for Technical Cooperation and Development; Adventist Development and Relief Agency; Amanda Magra Universal Relief Team; Catholic Relief Services; et al. (Food and Agriculture Organization of the United Nations, 2011)
Juba, South Sudan